2011
DOI: 10.1177/1350650111412706
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modelling and development of SiC-filled ZA-27 alloy composites in erosive wear environment: a comparative analysis

Abstract: The erosion wear resistance of silicon carbide (SiC) filled Zn–Al alloys is determined insolid particle erosive wear test rig under five different operation conditions such as impact velocity, SiC content, erodent temperature, impingement angle, and erodent size. This study evaluates the influence of independent parameters on erosive wear behaviour of composites. A design of experiments L16 orthogonal array design is conducted in a controlled way and a regression model is developed in order to verify the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…It has not been clarified how such combinations of a matrix material and a filler material affect the erosion characteristics of MMCs and CMCs. There has been no solid particle erosion data on newly developed advanced composite materials such as carbon based nano-reinforcements, CNTs, graphenes, and so on. Simulations studies on solid particle erosion of composites have been not yet enough done. 87, 119, 186188 Further studies will be needed to quantitative simulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has not been clarified how such combinations of a matrix material and a filler material affect the erosion characteristics of MMCs and CMCs. There has been no solid particle erosion data on newly developed advanced composite materials such as carbon based nano-reinforcements, CNTs, graphenes, and so on. Simulations studies on solid particle erosion of composites have been not yet enough done. 87, 119, 186188 Further studies will be needed to quantitative simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Mamatha et al. 119 performed solid particle erosion experiments of Zn-Al alloy reinforced by SiC particles (SiC/Zn-Al), and finite element simulations of erosion characteristics of the composites to validate experimental results. It was observed that the SiC/Zn-Al composites exhibited the better erosion resistance than unreinforced Zn-Al alloy.…”
Section: Metal Matrix Compositesmentioning
confidence: 99%
“…Table 2 gives the characteristics of both powders utilized in this research work. SiC has been used as reinforcement by different researchers (Izciler and Muratoglu 2003;Mamatha et al 2011). Si3N4 presents a higher hardness than SiC, due to which a harder casting is obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Similar, observations was observed for 2024 aluminum alloy MMCs with Al 2 O 3 filler particles, the density of the composites increased with increasing weight percentage and size of particles, whereas, the porosity of the composites increased with decreasing size and increasing weight percentage of particles. [23][24][25][26][27][28] Effect of varying wt.% of SiC on hardness of A356 alloy composite…”
Section: Effect Of Varying Wt% Of Sic On Void Content Of A356 Alloy Compositesmentioning
confidence: 99%